Field performance of BARI urea super granule applicator (Bangladesh Journal of Agricultural Research, 2016)
Field performance of BARI Urea Super Granule (USG) applicator was evaluated on BARI research stations (Gazipur, Pabna, and Barisal) and farmers field (Pabna, Barisal, Magura,Narshingdi,Jhenadah, Sirajgang, Rajbari and Jhalkathi) during the boro season of 2012-13. The applicator was tested with four treatments- application of USG by hand (165 kg/ha), application of USG by BARI USG applicator (165 kg/ha), application of prilled urea at USG rate (165 kg/ha) and application of prilled urea at farmers practice. In the farmers field, USG applicators were evaluated with the traditional broadcasting of granular urea. Similar yield of rice was obtained from machine and hand application of USG in all locations. Higher yield of rice was obtained from USG than granular urea. During field test, average field capacity and efficiency of the applicator were 0.138 ha/h and 81%, respectively. Considering custom hiring, the net income per year was Tk. 71750 and the payback period was 3 days. The price of the applicator is Tk. 3500.Bangladesh J. Agril. Res. 41(1): 103-113, March 2016